Environmental Risks in the News: A Qualitative Analysis of Spanish Television News programs - Espinar Ruiz, Eva; Samuelsson, Anna (Estudios sobre el Mensaje Periodístico, 2012)
Given the important role mass media play in the dissemination of risks, this article analysis the media discourse about a particular risk: the environmental one. From a sample of 84 news programs broadcast by the three Spanish television channels with the highest national ratings, we have analyzed a total of 138 pieces of news related to the environment and the nature. Applying qualitative methodology, the information has been classified looking for discourses around: references to environmental risks, causes, consequences and solutions. In general terms, news tend to focus on specific events and display their preference to emotional contents, entertainment or anecdotal facts, compared to the explanation of solutions, consequences and, above all, causes.